Development of the tropical fish Xenomelaniris brasiliensis (Pisces: Atherinidae) from embryo to larva and time to metamorphosis - del Río, Verónica (2005)
Embryonic-larval development, and metamorphosis larval time, were studied in the tropical fish Xenomelaniris brasiliensis. Twenty nine sexually mature specimens were used, 16 females (10.86 ± 1.01 cm and 7.63 ± 2.62 g) and 13 males (10.43 ± 0.57 cm and 6.54 ± 1.44 g) which produced gametes through abdominal massage. Fertilized eggs were spherical (1.18 ± 0.44 mm diameter), greenish, transparent, benthonic and vitelus-rich; rugose striated chorion with numerous external filaments randomly distributed and abundant oil globules (0.11 ± 0.07 mm diameter). The embryonic development was finished at 26.36 ± 2.03ºC, 39.67 ± 0.58 PSU and pH 8.30 ± 0.10. Larvae (4.56 ± 0.97 mm total length) hatched at 143 hours and 19 minutes, with vitteline sac vestiges and a single oil globule. The larvae were fed on Brachionus plicatilis and Isochrysis galbana. After the second week Artemia nauplii were added and I. galbana maintained. Flexion started 13 days after larvae hatched (6.10 ± 1.54 mm total length) and was completed 32 days later (11.25 ± 1.87 mm total length) with the hipural complex completely developed. In conclusion, X. brasiliensis showed direct larval development and started larval metamorphosis (13.08 ± 2.07 mm total length) to juvenile 40 days after hatching